Prevalence of treated hyper- and hypo-thyroidism and sociodemographic and geographic disparities in France in 2020 - Joël Coste; Laurence Mandereau-Bruno; Xavier Bertagna; Jean-Louis Wémeau (European Thyroid Journal, 2025)
Background: Healthcare claims data are increasingly used to investigate the epidemiology of benign thyroid diseases. Here, we estimate the prevalence of treated hyper- and hypo-thyroidism and assess the potential sociodemographic and geographic disparities in France in 2020, given the country’s poor epidemiological knowledge of these conditions. Methods: We used the French national healthcare data system, which covers nearly the entire population residing in France (over 67 million inhabitants in metropolitan and overseas departments). Prevalent cases were identified based on patients’ long-term disease status, hospitalisation for hyper- and hypo-thyroidism and reimbursements for thyroid hormones, antithyroid drugs, iodine-131 and thyroid surgery. Thyroid-stimulating hormone, antithyroid antibodies and previous therapy for thyroid cancer and hyperthyroidism were considered to characterise the origin and surveillance of hypothyroidism. Results: In 2020, we identified 112,992 and 2,986,333 cases of treated hyper- and hypo-thyroidism, respectively, with an overall prevalence of 0.17 and 4.45 per 100 inhabitants. Marked differences were observed in terms of sex, age group and geographic area (department) for both conditions and deprivation level of the place of residence for hyperthyroidism only. The proportion of hypothyroidism following previous therapy for thyroid cancer or hyperthyroidism was less than 10%. Adequate monitoring (thyroid-stimulating hormone checked in the past year) occurred in 73.7% of hypothyroid subjects, with large variations across departments. Conclusions: This study provides prevalence estimates of treated hyper- and hypo-thyroidism at the national and departmental levels in France and improves epidemiological knowledge of both conditions. It also supports using healthcare claims data for their epidemiological surveillance.